PENCAPAIAN MILLENIUM DEVELOPMENT GOALS (MDGs) DI INDONESIA MELALUI KERJASAMA INTERNASIONAL - Lisbet Lisbet (Jurnal Politica, 2013)
Indonesia has succeeded to achieve several target in the Millennium Development Goals (MDGs). There are other targets that need more effort to be achieved by the government. Because of this reason, the writer argues the country needs assistance. This paper says that the assistance can be done by increasing international cooperation not only with developed but also with developing countries.